All the women of the Bible; a portrait gallery and reference library. - Del Mastro, M. L. (Edison, New Jersey Castle Books, 2004)
A comprehensive history with more than 300 biographies--a feminine portrait gallery of saints, sorceresses, faithful mothers and wives, queens, and business women, the famous and infamous women of the Bible.
Bibliography: p. 373-374.
Keywords: Bible -- Biography -- Dictionaries; Women in the Bible -- Biography -- Dictionaries